Dissociation of retinal and headcentric disparity signals in dorsal human cortex - Arnoldussen, David M.; Goossens, Jeroen; van Den Berg, Albert V. (Frontiers in Systems Neuroscience, 2015)
Recent fMRI studies have shown fusion of visual motion and disparity signals for shape perception (Ban et al., 2012), and unmasking camouflaged surfaces (Rokers et al., 2009), but no such interaction is known for typical dorsal motion pathway tasks, like grasping and navigation. Here, we investigate human speed perception of forward motion and its representation in the human motion network. We observe strong interaction in medial (V3ab, V6) and lateral motion areas (MT+), which differ significantly. Whereas the retinal disparity dominates the binocular contribution to the BOLD activity in the anterior part of area MT+, headcentric disparity modulation of the BOLD response dominates in area V3ab and V6. This suggests that medial motion areas not only represent rotational speed of the head (Arnoldussen et al., 2011), but also translational speed of the head relative to the scene. Interestingly, a strong response to vergence eye movements was found in area V1, which showed a dependency on visual direction, just like vertical-size disparity. This is the first report of a vertical-size disparity correlate in human striate cortex.